The swapping approach in the course of land consolidation: case study of Ukraine - Malashevskyi, Mykola; Malashevska, Olena (Geodesy and Cartography, 2021)
The paper is concerned with the issues of the voluntary land consolidation using the exchange method at land relations reforming. The objective of the article is the substantiation of the exchange method aiming at the large and small land owners (land users) land tenure optimization and the formation of approaches with the help of which the mutual alignment of their interests can be achieved. Land plot ownership and tenure rights exchange by the relative value has been substantiated. It is suggested to define the relative value based on the principle of juxtaposition of land plots by their qualitative, spatial and technological characteristics. The land plots exchange modelling has been improved according to the relative value application and due to the existing land plots boundaries retaining at the exchange. The effectiveness of the suggested land plots exchange method has been demonstrated at the land tenure optimization of an agricultural enterprise and some households in Kyiv Region. Alternative land consolidation projects based on the land plots exchange have been developed, the results of which demonstrate the advantages of the voluntary land consolidation based on the suggested methodology.